2014
DOI: 10.1002/smll.201402354
|View full text |Cite
|
Sign up to set email alerts
|

A Revolution in Electrodes: Recent Progress in Rechargeable Lithium–Sulfur Batteries

Abstract: As a promising candidate for future batteries, the lithium-sulfur battery is gaining increasing interest due to its high capacity and energy density. However, over the years, lithium-sulfur batteries have been plagued by fading capacities and the low Coulombic efficiency derived from its unique electrochemical behavior, which involves solid-liquid transition reactions. Moreover, lithium-sulfur batteries employ metallic lithium as the anode, which engenders safety vulnerability of the battery. The electrodes pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
213
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(217 citation statements)
references
References 184 publications
(308 reference statements)
0
213
0
4
Order By: Relevance
“…The distribution of the cations between these two sites is highly dependent upon the nature of the cations incorporated into the structure. In normal spinels, the divalent A and trivalent B cations occupy the tetrahedral and octahedral sites, respectively, as in Co 3 4 . In addition to the electrical behaviour, the catalytic properties of spinel-type transition metal oxides towards chemical or electrochemical reactions (e.g., Co oxidation, oxygen reduction/evolution, and redox conversion of NO and CO mixtures) have been found to be determined by the nature of the surface, namely, the atomic arrangement and coordination on the oxide surface.…”
Section: General Aspects Of Spinel-type Transition Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the cations between these two sites is highly dependent upon the nature of the cations incorporated into the structure. In normal spinels, the divalent A and trivalent B cations occupy the tetrahedral and octahedral sites, respectively, as in Co 3 4 . In addition to the electrical behaviour, the catalytic properties of spinel-type transition metal oxides towards chemical or electrochemical reactions (e.g., Co oxidation, oxygen reduction/evolution, and redox conversion of NO and CO mixtures) have been found to be determined by the nature of the surface, namely, the atomic arrangement and coordination on the oxide surface.…”
Section: General Aspects Of Spinel-type Transition Metal Oxidesmentioning
confidence: 99%
“…Therefore, clean energy production from renewable energy sources such as solar, wind, and hydropower has been extensively studied by many researchers and scientists. [1][2][3][4][5] At the same time, the high demand for portable electronic devices, electric vehicles (EVs), and large-scale stationary energy storage systems will further promote the rapid growth of energy storage markets.…”
Section: Introductionmentioning
confidence: 99%
“…3). There have been several reviews that expand on these topics and can be found in the references [106][107][108][109][110][111][112][113][114][115][116][117][118] (Fig. 5).…”
Section: Fundamental Studies and Materials Selectionmentioning
confidence: 99%
“…Theoretically, the S cathode can deliver a specific energy of 2600 W h kg -1 , about five times higher than those of available insertion-materials of Li-ion batteries at a significantly lower cost [3]. The development of Li/S system faces several challenges such as low degree of sulphur utilization, gradual capacity fading, poor rate capability and low Coulombic efficiency mainly due to low conductivity of S8 (5 × 10 −30 S cm −1 ), solubility of intermediate polysulphides, shuttling of polysulphides and lack of morphology restoration at electrode reoxidation [4]. S8 cathode usually discharges in two plateaus;…”
Section: Introductionmentioning
confidence: 99%